2016
DOI: 10.1016/j.nlm.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating different representations in the hippocampus

Abstract: The processes that organize different thoughts and memories, allowing the separation of currently relevant and irrelevant information, are collectively known as cognitive control. The neuronal mechanisms of these processes can be investigated by place cell ensemble recordings during behaviors and environmental manipulations that present cognitive control challenges to selectively represent one of multiple possible alternative estimates of location. We review place cell studies that investigate responses to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 74 publications
(119 reference statements)
7
56
0
Order By: Relevance
“…24 for review). Furthermore, in tasks in which decisions depend on knowing one's position relative to a shifting goal, rodents are only able to find the goal or avoid the shock when the spatial representation in hippocampus is aligned to that goal's coordinate system 49,50 . An interesting question is whether hippocampus is necessary for deliberative, planning actions.…”
Section: Is There Clear Experimental Evidence That the Spatial Informmentioning
confidence: 99%
“…24 for review). Furthermore, in tasks in which decisions depend on knowing one's position relative to a shifting goal, rodents are only able to find the goal or avoid the shock when the spatial representation in hippocampus is aligned to that goal's coordinate system 49,50 . An interesting question is whether hippocampus is necessary for deliberative, planning actions.…”
Section: Is There Clear Experimental Evidence That the Spatial Informmentioning
confidence: 99%
“…There is rather large heterogeneity of place cell behaviors: some place cells “globally remap” (i.e., gain or lose place fields at given locations) while other place cells “rate remap” (i.e., maintain place field location but have consistently different firing rates under the different conditions). Moreover, rate remapping is not simply a long‐term average of an all‐or‐none firing phenomenon with a rate that depends on condition (Figure ), as would be expected if there were multiple maps that were being switched between, one in which the cell has a place field at that location and others in which it does not (Jackson & Redish, ; Kelemen & Fenton, ; Olypher et al, ). Rather, we show that even when restricting analysis to theta cycles on which a cell is active and therefore in the appropriate map, there are still firing rate changes between the conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, one theory that has been proposed to explain this excess variability provides an alternative interpretation of rate remapping. It has been shown that, for a task in which an animal must switch between maze and room cues, there are actually separate hippocampal maps for the two reference frames and the hippocampus switches between them in a task‐dependent way (Fenton et al, ; Kelemen & Fenton, ). It has been suggested that this process of map switching may actually be a more general phenomenon that occurs under all conditions and that the hippocampus switches between maps at a frequency of 1–10 Hz (Olypher, L'ansky, & Fenton, ; Jackson & Redish, ; Jezek, Henriksen, Treves, Moser, & Moser, ).…”
Section: Introductionmentioning
confidence: 99%
“…One clue is that map switching can occur as fast as at the subsecond timescale (Harris et al, ; Jackson & Redish, ; Jezek et al, ; Kelemen & Fenton, ; Kelemen & Fenton, ) and is thus temporally flexible enough to support a rapidly evolving ongoing behavioral need. It has been argued before that the interlinking of multiple maps through switching allows for flexible recall of similar experiences for the sake of effective problem solving, particularly in circumstances requiring inference (e.g., goal‐directed navigation; Cohen & Eichenbaum, ; Eichenbaum et al, ; Eichenbaum & Cohen, ).…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%